St. Lucia : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
St. Lucia showed strong growth performance owing to its strong investment in tourism infrastructure. Executive Directors commended the prudent public debt management and sound banking system. They underscored the need for fiscal consolidation and steps to promote domestic investment and labor market flexibility. They appreciated the well-designed disaster prevention and mitigation framework, and urged the need to reduce unemployment, reverse the rapid rise in public debt, and encouraged authorities to improve the timeliness and accuracy of data for economic analysis and policymaking.